2018
DOI: 10.1186/s40709-018-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

New marine gastropod records for the Hellenic waters

Abstract: BackgroundThe Hellenic Seas are influenced by on-going environmental changes and the introduction of alien species, which are expected to have an impact on their biodiversity. This study contributes to the knowledge of the Hellenic marine gastropod biodiversity, expanding data over the entire Greek territory, during the period from October 2008 to March 2017.ResultsThis work presents 45 species of gastropods not previously reported from Greece or reported only once, belonging to 19 families. From those species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This work raises the Hellenic gastropod biodiversity from 654 species [ 28 , 32 , 49 – 51 ] to 664 species, while the Raphitomidae family is enriched by 45%.…”
Section: Discussionmentioning
confidence: 99%
“…This work raises the Hellenic gastropod biodiversity from 654 species [ 28 , 32 , 49 – 51 ] to 664 species, while the Raphitomidae family is enriched by 45%.…”
Section: Discussionmentioning
confidence: 99%
“…(2020); 8—Lykakis and Kalathakis (1991); 9—Katsanevakis (2005); 10—Mannousis et al . (2010); 11—Sealifebase; 12—FAO; 13—EOL (Encyclopaedia of Life); 14—Ocean Biogeographic Information System; 15—Katsanevakis et al . (2008); 16—Hrs‐Brenko and Legac (1996); 17—Koutsoubas et al .…”
Section: Distribution Of Edible Bivalve Species and Pathogens Along T...mentioning
confidence: 99%
“…Since then, new species have been recorded in the Hellenic Seas (Kondylatos et al, 2018;Dragičević et al, 2019;Kousteni et al, 2019;Küpper et al, 2019;Giovos et al, 2020;Karachle et al in Bariche et al, 2020;Angelidis & Polyzoulis, 2018;Manousis et al, 2020;Pirkenseer, 2020;Ragkousis et al, 2020;Zenetos & Miliou, 2020;. In addition, several NIS have extended their distribution range northwards (Aegean Sea) (Gerovasileiou et al, 2017;Kondylatos & Corsini-Foka, 2017;Lipej et al, 2017;Ulman et al, 2017;Chartosia et al, 2018;Manousis et al, 2018) and westwards (Ionian Sea) (Yokeş et al, 2018;Dimitriadis et al, 2019Dimitriadis et al, , 2020Pirkenseer, 2020). Unaided natural dispersal of NIS previously introduced elsewhere in the Mediterranean (58%) and transport-stowaway (37.1%) were identified as the major pathways of introduction for the new NIS introduced into Hellenic waters (Zenetos et al, 2018), following similar patterns to those observed in the Eastern Mediterranean Sea (Katsanevakis et al, 2013;Armon & Zenetos, 2015).…”
Section: Introductionmentioning
confidence: 99%